A method for preparing electromagnetic shielding aramid film
By ultrasonic dispersing para-aramid nanofibers and multi-walled carbon nanotubes in deionized water and electroplating in the plating solution, an electromagnetic shielded aramid film was prepared, which solved the shortcomings of existing electromagnetic shielding materials in taking into account both electromagnetic shielding and mechanical properties, and achieved a significant improvement in electromagnetic shielding performance.
Patent Information
- Application Number
- CN202411789282.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-08
AI Technical Summary
The existing electromagnetic shielding materials have shortcomings in taking into account both electromagnetic shielding and mechanical properties, which makes them difficult to be widely used in practical applications.
Electromagnetic shielded aramid film was prepared by ultrasonic dispersing para-aramid nanofibers and multi-walled carbon nanotubes in deionized water and electroplating in the plating solution. This method not only maintains the excellent mechanical properties of aramid materials, but also significantly improves the electromagnetic shielding performance.
The electromagnetic shielding performance is significantly improved on the basis of maintaining mechanical properties, so that the prepared electromagnetic shielding aramid film has significant technical effects in the field of electromagnetic shielding.
Smart Images

Figure BDA0005174926280000061
Abstract
Description
Technical Field
[0001] The invention relates to the field of new materials, and in particular to a method for preparing an electromagnetic shielding aramid film. Background Art
[0002] Electromagnetic shielding film is a shielding material that can block the penetration of electromagnetic waves, prevent electromagnetic radiation, protect electronic components, and resist electromagnetic interference. Current electrical and electronic equipment will radiate a large amount of electromagnetic waves during use. Alleviating or blocking the pollution caused by electromagnetic radiation has become an important research direction in the field of materials science.
[0003] Para-aramid fiber (also known as Kevlar) is a synthetic fiber prepared by compounding terephthaloyl chloride and paraphenylenediamine (PPTA). Its molecular structure is highly symmetrical, and there are obvious interactions between molecules (hydrogen bonds, van der Waals forces and 7c. Wu effects). In addition, there is a special chemical structure, which makes aramid fiber (AF) have the characteristics of chemical corrosion resistance, excellent mechanical properties, easy processing and excellent high temperature resistance. Aramid nanofibers are light, non-toxic and pollution-free, have strong environmental adaptability and strong molecular designability. They are ideal matrix materials in many fields including paper products, electronic and electrical and functional materials. At present, the application of aramid nanofibers is mainly concentrated in filtration, adsorption, and supercapacitors. But it itself is not conductive and has a very poor shielding effect on electromagnetic radiation. However, some researchers use it as a filler to enhance the mechanical properties of electromagnetic shielding materials. However, since the amount of aramid nanofiber added as a filler cannot exceed the matrix material, the prepared composite material has excellent electromagnetic shielding effectiveness, but its overall mechanical properties are difficult to meet the requirements and cannot be widely used in practical applications.
[0004] Therefore, it is of great significance to design an electromagnetic shielding material with excellent comprehensive performance by combining the electromagnetic shielding performance and mechanical properties of composite materials. Summary of the invention
[0005] In view of the problems of the prior art, the present invention provides a method for preparing an electromagnetic shielding aramid film. The materials used in the method of the present invention are para-aramid nanofibers, multi-walled carbon nanotubes, and electroplating solution. On the basis of maintaining the excellent mechanical properties of the aramid material, the electromagnetic shielding performance is effectively improved, and the method can be applied to the field of electromagnetic shielding, with significant technical effects.
[0006] In order to achieve the above object, the present invention provides a method for preparing an electromagnetic shielding aramid film, the specific steps of which include:
[0007] (1) Preparation of aramid membrane: Aramid nanofibers and multi-walled carbon nanotubes are ultrasonically dispersed in deionized water according to a certain proportion, filtered, and pressed into membrane;
[0008] (2) Preparation of plating solution: The plating solution is a potassium pyrophosphate system, and copper compounds, nickel compounds, and leveling agents are added;
[0009] (3) electroplating the aramid film in a plating solution;
[0010] (4) The electroplated material is washed with water and flattened with a press.
[0011] Preferably, in step (1), the mass ratio of aramid nanofibers to multi-walled carbon nanotubes is 1:(0.1-0.3), and the multi-walled carbon nanotubes have a diameter of 8-30 nm and a length of 1-20 um.
[0012] Preferably, the ultrasonic dispersion conditions in step (1) are: ultrasonic power 1000-1500w, ultrasonic time 30-60min.
[0013] Preferably, the film pressing conditions in step (1) are: a press temperature of 100-150°C, a press pressure of 100-200 kgf / cm 2 , pressing time 60-90min.
[0014] Preferably, the multi-walled carbon nanotubes may be subjected to a dispersion pretreatment before step (1): a dispersant is added to deionized water, stirred evenly, and then the multi-walled carbon nanotubes are added for ultrasonic treatment.
[0015] More preferably, the concentration of the dispersant in deionized water is 0.2-1 g / L.
[0016] More preferably, the dispersant is selected from one or more of SDS, MSDS and the like.
[0017] Preferably, the mass ratio of the multi-walled carbon nanotubes to the dispersant is 1:(0.1-0.5), the ultrasonic power is 1000-1500w, and the ultrasonic time is 30-60min.
[0018] Preferably, in the plating solution of step (2), the concentration of potassium pyrophosphate is 100-150 g / L, the concentration of copper compound is 20-40 g / L, the concentration of nickel compound is 5-10 g / L, and the concentration of leveler is 1-5 ppm.
[0019] More preferably, the copper compound in step (2) is selected from basic copper carbonate, copper sulfate, copper chloride and the like.
[0020] More preferably, the nickel compound described in step (2) is selected from nickel sulfate, nickel chloride, etc.
[0021] More preferably, the leveling agent in step (2) is selected from SPS, thiourea, PEG, cellulose and the like.
[0022] More preferably, the pH of the plating solution in step (2) is 9.0-10.0.
[0023] Preferably, the plating solution temperature in step (3) is 20-25°C.
[0024] Preferably, the electroplating anode in step (3) is a titanium plate, and the electroplating current density is 1-5A / dm 2 , electroplating time 1-5min.
[0025] Preferably, the conditions of the press in step (4) are 120-150°C, 1.5-3h, and a pressure of 50-100Kgf / cm 2 .
[0026] The beneficial effects of the present invention are:
[0027] The technical solution of the present invention not only uses multi-walled carbon nanotubes to directly participate in the film-forming process of the aramid film, so that the dispersion and distribution of the multi-walled carbon nanotubes in the aramid film are more uniform, but also uses a plating solution to electroplate the aramid film, thereby further improving the electromagnetic shielding effect. Compared with the aramid film modified only by multi-walled carbon nanotubes in the prior art, the electromagnetic shielding effect is better. Compared with the technical solution of electroplating only carbon nanotubes in the prior art, the present invention electroplates the aramid film, and the plating solution coating is more uniform and the thickness is easy to control. DETAILED DESCRIPTION
[0028] The above contents of the present invention are further described in detail below through specific implementation methods, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies implemented based on the above contents of the present invention belong to the scope of the present invention. Unless otherwise specified, the following embodiments are all completed using conventional existing technologies.
[0029] The main reagents used in the following examples are: para-aramid nanofibers purchased from Shandong Jufang New Materials Co., Ltd., multi-walled carboxyl carbon nanotubes purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with specifications of 95% purity, less than 10 μm in length, and 0.49 wt% carboxyl content; multi-walled amino carbon nanotubes purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with specifications of outer diameter 8-15 nm and length ≤20 μm; potassium pyrophosphate purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.; basic copper carbonate purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.; copper sulfate purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.; nickel sulfate purchased from Thermo Fisher Scientific (China) Co., Ltd.; nickel chloride purchased from Henan Yiquan Chemical Technology Co., Ltd.
[0030] Example 1
[0031] (1) Pretreatment of multi-walled carbon nanotube dispersion: 0.01 g SDS was added into 50 ml deionized water, stirred evenly, and then 0.1 g multi-walled carboxyl carbon nanotubes were added, followed by ultrasonic treatment at an ultrasonic power of 1000 W for 30 min.
[0032] (2) Preparation of aramid membrane: 1 g of aramid nanofibers was ultrasonically dispersed with multi-walled carbon nanotubes at an ultrasonic power of 1000 W and an ultrasonic time of 30 min. The membrane was then filtered and pressed at a press temperature of 100 °C and a press pressure of 100 kgf / cm 2 , press time 60min.
[0033] (3) Prepare the plating solution: potassium pyrophosphate system, wherein the concentration of potassium pyrophosphate is 100 g / L, the concentration of basic copper carbonate is 20 g / L, the concentration of nickel sulfate is 5 g / L, and the concentration of SPS is 1 ppm; the pH of the system is 9.0.
[0034] (4) The aramid film is electroplated in a plating solution at a temperature of 20°C, the electroplating anode is a titanium plate, and the electroplating current density is 1 A / dm 2 , electroplating time 1min.
[0035] (5) The electroplated material is washed with water and pressed flat. The pressing conditions are 120°C, 1.5h, and a pressure of 50Kgf / cm 2 .
[0036] Example 2
[0037] (1) Pretreatment of multi-walled carbon nanotube dispersion: 0.05 g MSDS was added into 50 ml deionized water, stirred evenly, and then 0.1 g multi-walled amino carbon nanotubes were added. The mixture was ultrasonically treated at an ultrasonic power of 1500 W and an ultrasonic time of 60 min.
[0038] (2) Preparation of aramid membrane: 0.33 g of aramid nanofibers were ultrasonically dispersed with multi-walled amino carbon nanotubes at an ultrasonic power of 1500 W and an ultrasonic time of 60 min. The membrane was then filtered and pressed at a press temperature of 150 °C and a press pressure of 200 kgf / cm 2 , press time 90min.
[0039] (3) Prepare the plating solution: potassium pyrophosphate system, wherein the concentration of potassium pyrophosphate is 150 g / L, the concentration of copper sulfate is 40 g / L, the concentration of nickel chloride is 10 g / L, and the concentration of thiourea is 5 ppm; the pH is 10.0.
[0040] (4) The aramid film is electroplated in a plating solution at a temperature of 25°C, the electroplating anode is a titanium plate, and the electroplating current density is 5A / dm 2 , electroplating time 5min.
[0041] (5) The electroplated material is washed with water and pressed flat. The pressing conditions are 150°C, 3h, and a pressure of 100Kgf / cm 2 .
[0042] Example 3
[0043] (1) Pretreatment of multi-walled carbon nanotube dispersion: 0.03 g SDS was added into 50 ml deionized water, stirred evenly, and then 0.1 g multi-walled carboxyl carbon nanotubes were added, followed by ultrasonic treatment at an ultrasonic power of 1000 W for 30 min.
[0044] (2) Preparation of aramid membrane: 1 g of aramid nanofibers was ultrasonically dispersed with multi-walled carbon nanotubes at an ultrasonic power of 1000 W and an ultrasonic time of 30 min. The membrane was then filtered and pressed at a press temperature of 150 °C and a press pressure of 100 kgf / cm 2 , press time 90min.
[0045] (3) Prepare a plating solution: a potassium pyrophosphate system, wherein the concentration of potassium pyrophosphate is 140 g / L, basic copper carbonate is 30 g / L, nickel chloride is 7 g / L, and thiourea concentration is 3 ppm. The pH of the system is 9.5.
[0046] (4) The aramid film is electroplated in a plating solution at a temperature of 25°C, the electroplating anode is a titanium plate, and the electroplating current density is 3A / dm 2 , electroplating time 4min.
[0047] (5) The electroplated material is washed with water and pressed flat. The pressing conditions are 130°C, 2h, and a pressure of 90Kgf / cm 2 .
[0048] Comparative Example 1
[0049] (1) Pretreatment of multi-walled carbon nanotube dispersion: 0.01 g SDS was added into 50 ml deionized water, stirred evenly, and then 0.1 g multi-walled carboxyl carbon nanotubes were added, followed by ultrasonic treatment at an ultrasonic power of 1000 W for 30 min.
[0050] (2) Preparation of aramid membrane: 1 g of aramid nanofibers was ultrasonically dispersed with multi-walled carbon nanotubes at an ultrasonic power of 1000 W and an ultrasonic time of 30 min. The membrane was then filtered and pressed at a press temperature of 100 °C and a press pressure of 100 kgf / cm 2 , press time 60min.
[0051] (3) The material was washed with water and flattened by a press under the following conditions: 120°C, 1.5h, and a pressure of 50Kgf / cm 2 .
[0052] Comparative Example 2
[0053] (1) Pretreatment of multi-walled carbon nanotube dispersion: 0.05 g MSDS was added into 50 ml deionized water, stirred evenly, and then 0.1 g multi-walled amino carbon nanotubes were added. The mixture was ultrasonically treated at an ultrasonic power of 1500 W and an ultrasonic time of 60 min.
[0054] (2) Preparation of aramid membrane: 0.33 g of aramid nanofibers were ultrasonically dispersed with multi-walled amino carbon nanotubes at an ultrasonic power of 1500 W and an ultrasonic time of 60 min. The membrane was then filtered and pressed at a press temperature of 150 °C and a press pressure of 200 kgf / cm 2 , press time 90min.
[0055] (3) Prepare the plating solution: potassium pyrophosphate system, wherein the concentration of potassium pyrophosphate is 200 g / L, the concentration of copper sulfate is 100 g / L, the concentration of nickel chloride is 10 g / L, and the concentration of thiourea is 5 ppm; the pH is 10.0.
[0056] (4) The aramid film is electroplated in a plating solution at a temperature of 25°C, the electroplating anode is a titanium plate, and the electroplating current density is 5A / dm 2 , electroplating time 5min.
[0057] (5) The electroplated material is washed with water and pressed flat. The pressing conditions are 150°C, 3h, and a pressure of 100Kgf / cm 2 .
[0058] Comparative Example 3
[0059] (1) Pretreatment of multi-walled carbon nanotube dispersion: 0.03 g SDS was added into 50 ml deionized water, stirred evenly, and then 0.1 g multi-walled carboxyl carbon nanotubes were added, followed by ultrasonic treatment at an ultrasonic power of 1000 W for 30 min.
[0060] (2) Preparation of aramid membrane: 1 g of aramid nanofibers was ultrasonically dispersed with multi-walled carbon nanotubes at an ultrasonic power of 1000 W and an ultrasonic time of 30 min. The membrane was then filtered and pressed at a press temperature of 150 °C and a press pressure of 100 kgf / cm 2 , press time 90min.
[0061] (3) Prepare a plating solution: a potassium pyrophosphate system, wherein the concentration of potassium pyrophosphate is 140 g / L, basic copper carbonate is 30 g / L, nickel chloride is 7 g / L, and thiourea concentration is 3 ppm. The pH of the system is 9.5.
[0062] (4) The aramid film is electroplated in a plating solution at a temperature of 25°C, the electroplating anode is a titanium plate, and the electroplating current density is 0.3 A / dm 2 , electroplating time 2min.
[0063] (5) The electroplated material is washed with water and pressed flat. The pressing conditions are 130°C, 2h, and a pressure of 90Kgf / cm 2 .
[0064] Table 1 Comparison of dielectric constant and other properties
[0065]
[0066] The embodiments described above are merely descriptions of preferred implementation modes of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary engineering technicians in the field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing an electromagnetic shielding aramid film, characterized in that: The specific steps include: (1) Preparation of aramid membrane: Aramid nanofibers and multi-walled carbon nanotubes are ultrasonically dispersed in deionized water according to a certain proportion, filtered, and pressed into membrane; (2) Preparation of plating solution: The plating solution is a potassium pyrophosphate system, and copper compounds, nickel compounds, and leveling agents are added; (3) electroplating the aramid film in a plating solution; (4) Washing the electroplated material with water and flattening it with a press; In step (1), the mass ratio of aramid nanofibers to multi-walled carbon nanotubes is 1:(0.1-0.3).
2. The method for preparing an electromagnetic shielding aramid film according to claim 1, characterized in that: The multi-walled carbon nanotubes described in step (1) have a diameter of 8-30 nm and a length of 1-20 um.
3. The method for preparing an electromagnetic shielding aramid film according to claim 1, characterized in that: The ultrasonic dispersion conditions described in step (1) are: ultrasonic power 1000-1500w, ultrasonic time 30-60min.
4. The method for preparing an electromagnetic shielding aramid film according to claim 1, characterized in that: The film pressing conditions described in step (1) are: press temperature 100-150°C, press pressure 100-200kgf / cm 2 , pressing time 60-90min.
5. The method for preparing an electromagnetic shielding aramid film according to claim 1, characterized in that: The plating solution in step (2) has a potassium pyrophosphate concentration of 100-150 g / L, a copper compound concentration of 20-40 g / L, a nickel compound concentration of 5-10 g / L, and a leveler concentration of 1-5 ppm.
6. The method for preparing an electromagnetic shielding aramid film according to claim 1, characterized in that: The copper compound described in step (2) is selected from basic copper carbonate, copper sulfate, and copper chloride; the nickel compound is selected from nickel sulfate and nickel chloride; and the leveling agent is selected from SPS, thiourea, PEG, and cellulose.
7. The method for preparing an electromagnetic shielding aramid film according to claim 1, characterized in that: The pH of the plating solution in step (2) is 9.0-10.0; the temperature of the plating solution in step (3) is 20-25°C, the electroplating anode in step (3) is a titanium plate, and the electroplating current density is 1-5A / dm 2 , electroplating time 1-5min; step (4) press conditions are, 120-150 ° C, 1.5-3h, pressure 50-100Kgf / cm 2 .
8. The method for preparing an electromagnetic shielding aramid film according to claim 1, characterized in that: Before step (1), the multi-walled carbon nanotubes are dispersed and pre-treated: a dispersant is added to deionized water, stirred evenly, and then the multi-walled carbon nanotubes are added for ultrasonic treatment. The mass ratio of the multi-walled carbon nanotubes to the dispersant is 1:(0.1-0.5).
9. The method for preparing an electromagnetic shielding aramid film according to claim 7, characterized in that: The concentration of the dispersant in deionized water is 0.2-1 g / L; the dispersant is selected from one or more of SDS and MSDS; the ultrasonic power is 1000-1500w, and the ultrasonic time is 30-60min.
10. An electromagnetic shielding aramid film prepared according to the method according to any one of claims 1 to 9.
Citation Information
Cited By
Two-dimensional copper nanosheet / graphene / aramid fiber composite film material and preparation method and application thereof
CN120865586A